Analysis of Savings Asset Ownership and Duration of Illness on Ability to Purchase First-Level Health Care Facility Services in Jambi City - Dwi Noerjoedianto; Andi Subandi; Andy Amir (International Journal of Health Engineering and Technology, 2022)
To analyze ownership of savings assets and duration of illness on the ability to purchase first-level health care facilities in Jambi City.  This study used a cross sectional design. The research instrument used a questionnaire to 100 independent Non- Assistance Recipients (PBI) BPJS participants with accidental sampling technique. This research data is analyzed quantitatively.  Statistical test shows that there is a relationship between ownership of savings assets and purchasing ability (p value=0.003) and there is no relationship between duration of illness and ability to buy (pvalue=1,000).  There is a relationship between ownership of savings assets and there is no relationship between length of illness and ability to buy. It is expected that first-level health care fasilities with BPJS Health will assist in collecting data on independent JKN participants who cannot afford to pay to convert their membership into PBI participants and disseminate information about JKN to the community in the working area of the Public Health Centre (Puskesmas)